Dysfunctional uterine bleeding - Soszka, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Dysfunctional uterine bleedings (DUB) are all these abnormal uterine bleedings (AUB) after exclusion of anatomical and organic lesions as well as systemic and iatrogenic changes and pregnancy. In the presented paper special attention was paid to the diagnostic and therapeutic treatment in an outpatient clinic, including the patient interaction in the process. State-of the-art knowledge on the menstrual cycle pathophysiology and DUB has been presented basing on the angiogenesis model. The participation of many biologically active substances (including among others: kinins, endothelins, coagulation and fibrinolytic factors, prostanoids and platelet factors) in breakdown and regenerative processes within functional layers of the endometrium has been described. The regulative role of steroid hormones (estrogens, progesterone, activin-follistatin) was taken into consideration. The carefully taken medical history, the proper selection of diagnostic tools followed by the discussion with the patient on the pharmacological or, if desired, surgical options constitutes the whole treatment process in the case of troublesome DUB. In the paper new diagnostic and therapeutic methods including a wide range of scanning techniques, endometrial sampling and endometrial resection as well as ablation techniques have been presented. Special attention was paid to outpatient clinic methods (e.g. Pipella, minihysteroscopy, thermal ablation, photodynamic ablation and cryoablation). The pharmaceutical treatment depends on the intensity of bleeding (acute or chronic) and consists of estrogens, oral, transdermal and vaginal contraceptives, IUD system, progestin-oestrogen injections, Danazol and GnRH. Besides the hormones, non-steroid anti-inflammatory and antifibrinolytic drugs appeared to be effective in the treatment of DUB. One has to pay attention to menarche which in some ways reflects the proper local and systemic haemostatic mechanisms. Basing on these observations one may to decide to widen the diagnosis towards the haematological and/or endocrinological laboratories.